USULAN PERBAIKAN LINTASAN KERJA DENGAN PENDEKATAN PETA KELOMPOK KERJA DAN MODEL MATEMATIS PADA LINI PENGEMASAN PRODUK JELLYGUM DI PT MAKMUR ARTHA SEJAHTERA - Alawi, Adnan
PT Makmur Artha Sejahtera (PT MAS) is a company that produces jeli and beverages with markets both domestically and internationally. As a Fast-Moving Consumer Goods (FMCG) company, accuracy in meeting demand is one of the crucial factors to consider for its products to compete in the market. PT MAS faces issues related to the packing target for each shift, which often fails to reach the set target. PT MAS is limited in equipment and workers, making its production capacity dependent on packing capabilities. As a result, when demand is high, PT MAS often struggles to meet production as planned by the Production Planning Inventory Control (PPIC) department. Based on 2023 historical production data, the jellygum product has the highest demand. Therefore, this study discusses the grouping of work elements and improvement of work methods in the jellygum packaging line to address this issue. This study proposes the grouping of work elements and improvement of work methods in the jellygum packaging line to minimize the packing process cycle time. The study uses a gang process chart approach and a mathematical model of the Assembly Line Balancing Problem Type-II (ASLBP-II). The gang process chart approach is used to solve the problem by testing all possibilities that can provide the most satisfactory result. At the same time, the mathematical model employs an analytical approach to solve the problem, leading to an optimal solution. From the study results, three work method improvement proposals for the jellygum packaging line were provided. In the first proposal, the cycle time achieved is 32.01 seconds with 14 workers assigned, in the second proposal, the cycle time is 49.07 seconds with 16 workers assigned, and in the third proposal, the cycle time is 29.24 seconds with 18 workers assigned.